An area of untapped potential? The use of restorative justice in the fight against serious and organized crime: A perception study. (April 2021) - D'Souza, Nikki; L'Hoiry, Xavier
This article presents the results of a perception study which examined the potential for deploying restorative justice (RJ) in the context of serious and organized crime (SOC) offending. This is a hitherto unexplored area of debate and the study sought to engage the key stakeholders in RJ processes – victims, offenders and practitioners – to gather their views as to the suitability and desirability of extending RJ in this way. Employing a mixed methods approach, the study engaged over 40 participants across the three stakeholder groups. The findings challenge existing, deeply embedded orthodoxies concerning the very nature of SOC offending and offenders' motivations, as well confirming the multiplicity of SOC victims' expectations. The findings also demonstrate the urgent need for further debate concerning how best to account for the complexity of SOC victims' needs which are currently unmet by the systemic limits of the criminal justice system.